High penetrances of BRCA1 and BRCA2 mutations confirmed in a prospective series - Møller Pål (Hereditary Cancer in Clinical Practice, 2010)
Abstract Penetrances of BRCA1 and BRCA2 mutations have been derived from retrospective studies, implying the possibility of ascertainment biases to influence the results. We have followed women at risk for breast and/or ovarian cancer for two decades, and report the prospectively observed age-related annual incidence rates to contract breast or ovarian cancer for women with deleterious BRCA1 or BRCA2 mutations based on 4830 observation years. Patients were grouped according to mutation, age and having/not having had previous cancer. In women not having had previous cancer and aged 40-59 years, the annual incidence rate to contract breast or ovarian cancer in those having the most frequent BRCA1 founder mutations was 4.0%, for women in this age group and with less frequent BRCA1 mutations annual incidence rate was 5.9%, and for women with BRCA2 mutations 3.5%. The observed figures may be used for genetic counseling of healthy mutation carriers in the respective age groups. The results may indicate that less frequent BRCA1 mutations have higher penetrances than BRCA1 founder mutations.